2018
DOI: 10.1200/jco.2017.74.3179
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific T-Cells Engineered to Overcome Tumor Immune Evasion Induce Clinical Responses in Patients With Relapsed Hodgkin Lymphoma

Abstract: Purpose Transforming growth factor-β (TGF-β) production in the tumor microenvironment is a potent and ubiquitous tumor immune evasion mechanism that inhibits the expansion and function of tumor-directed responses; therefore, we conducted a clinical study to discover the effects of the forced expression of a dominant-negative TGF-β receptor type 2 (DNRII) on the safety, survival, and activity of infused tumor-directed T cells. Materials and Methods In a dose escalation study, eight patients with Epstein Barr vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 36 publications
1
116
0
Order By: Relevance
“…In light of the recently reported clinical utility of shielding adoptive T‐cell therapies from TGF‐β, further exploration of TGF‐β countermeasures are warranted. We previously demonstrated that TGF‐β–binding CARs can be engineered to rewire Teff cells to proliferate and produce immunostimulatory cytokines in response to soluble TGF‐β, effectively inverting an immunosuppressive signaling molecule to a potent T‐cell stimulant that triggers immunosupportive functions .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In light of the recently reported clinical utility of shielding adoptive T‐cell therapies from TGF‐β, further exploration of TGF‐β countermeasures are warranted. We previously demonstrated that TGF‐β–binding CARs can be engineered to rewire Teff cells to proliferate and produce immunostimulatory cytokines in response to soluble TGF‐β, effectively inverting an immunosuppressive signaling molecule to a potent T‐cell stimulant that triggers immunosupportive functions .…”
Section: Discussionmentioning
confidence: 98%
“…For example, monoclonal antibodies targeting TGF‐β and TGF‐β receptor chain 2 (TGFBR2) have been extensively studied in preclinical and early‐phase clinical studies . Other studies have more specifically targeted TGF‐β signaling within the tumor microenvironment with a TGF‐β dominant‐negative receptor (TGF‐β DNR), which renders transduced tumor‐specific T cells unresponsive to TGF‐β . We recently described a novel CAR that responds to TGF‐β (TGF‐β CAR), demonstrating the ability to not only inhibit endogenous TGF‐β signaling in T cells but also convert TGF‐β into a potent T‐cell stimulant .…”
Section: Introductionmentioning
confidence: 99%
“…35 Chimeric antigen receptor T cells have also been modified to express immune-stimulatory molecules to influence their interaction with other cell types within the local TME. 39 Overall, these studies suggest that therapeutic responses against solid tumors can potentially be augmented by engineering CAR T cells to express additional mediators that boost their local effector function and alter their interaction with surrounding cells in the TME. Furthermore, CD40 ligand directly engaged CD40-expressing tumor cells to alter their immunogenicity through the upregulation of surface receptors including MHC molecules and Fas ligand.…”
Section: Localised Expression Of Immune-stimulatory Molecules By Car mentioning
confidence: 97%
“…CAR-T cells containing multiple gene edits that include knockout of inhibitory signaling receptors such as PD-1 (PDCD1) [29,30], LAG-3 [31], or knock-in of a dominant negative TGFβ2R (TGFBR2) [32] have been described and are expected to enter into clinical trials in the near future.…”
Section: Additional Gene Edits To Reduce Immunogenicity and Resist Sumentioning
confidence: 99%